Consumers’ Perceived Value of Pork Meat: A Segmentation on Intrinsic and Extrinsic Cues - Diewald Jordaan; Annchen Mielmann; Carike Brits (Foods)
This study aimed to determine the intrinsic and extrinsic product cues affecting consumers’ perceived value of pork meat. A segmentation study of seventeen intrinsic (n = 103) and twenty-six extrinsic cues (n = 114) on a South African sample was implemented. Cluster analyses provided two consumer segments for the product cues: the sensory seekers and the indecisive consumers for the intrinsic cues, and the price seekers and the preparation inquirers for the extrinsic cues. The sensory seekers valued the visual appearance, odour, taste, and flavour of pork as moderately to very important. The preparation inquirers regarded all the extrinsic cues, except for the processing cues, as moderately to very important. Accentuating the importance of sensory and preparation cues in pork meat products may contribute to improving the quality of products. This paper highlights that more research is needed on how consumers could benefit from the cue-adjusted pork meat products that will influence their perceived value of this affordable and versatile food in the South African context.